Should the Use of Automated License Plate Readers Constitute a Search After Carpenter v. United States? - Stephanie Foster (Washington University Law Review, 2019)
This Note will analyze whether the use of information collected by automated license plate readers should be considered a search under the Fourth Amendment in light of the Supreme Court’s recent identification of a right to privacy in the whole of an individual’s movements. Given that automated license plate readers can reveal so many intimate details about our lives, is there a reasonable expectation of privacy with regard to the use of this information? Should a query of the aggregated data stored for each license plate be considered a search under the Fourth Amendment? Are there sufficient parallels between cell-site location information and automated license plate reader data so that a conclusion similar to that in Carpenter will be reached regarding automated license plate readers? This Note will argue that the answer to all of these questions is yes.
Keywords: Privacy law; Criminal law; License plate readers; Carpenter v. United States 138 S. Ct. 2206 (2018); Fourth amendment